Brønsted acid catalyzed hydroamination and its application to total synthesis of cuspareine - Bay, Siew Ting (2010)
An efficient method for the construction of 1,2-dihydroquinolines and its application to the total synthesis of cuspareine are reported herein. The method proceeds by protonation of the unactivated alkene, followed by an intramolecular cyclization with H2O as potentially the only by-product.